Multiphoton microscopy: applications in Urology and Andrology - Katz, Matthew J.; Huland, David M.; Ramasamy, Ranjith (Translational Andrology and Urology, 2014)
Multiphoton microscopy (MPM) enables real-time imaging of various cellular processes at submicron resolution. MPM is currently being used in neuroscience, oncology, and immunology. MPM has demonstrated promising results in urology. MPM has been used in the identification of spermatogenesis, evaluation of bladder cancer, and tissue identification in prostate cancer surgery. MPM has allowed the visualization of seminiferous tubules within the testis in a rat model and identified areas of spermatogenesis. MPM could potentially improve the efficacy of testicular sperm extraction. In bladder cancer evaluation, MPM has proven to be an effective imaging tool in identifying areas suspicious for malignancy. The imaging technology could be utilized in the future to provide urologists with an immediate impression of extracted bladder tissue, or as part of a cystoscopic device to evaluate the bladder in real time. Similarly, MPM has proven to be a useful imaging technique to evaluate prostate cancer. MPM could be utilized during a prostatectomy to help differentiate prostate from cavernous nerves that are closely adherent to the prostate. MPM uses a laser and safety studies will need to be performed prior to its utilization in the clinical setting.